2022
DOI: 10.1371/journal.pone.0271229
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with resilience among children and youths with disability during the COVID-19 pandemic

Abstract: There is evidence of negative impact of social distancing and confinement measures to manage the COVID-19 pandemic on children, including increased anxiety and depression and behaviour difficulties. Paradoxically, positive impacts like increased support and more self-care activities have also been documented. Little is known about the impact of the COVID-19 pandemic on the children with disability and the potential role of familial, environmental, and biological factors on mitigating this impact. The aims of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Mental health challenges were experienced by parents and children with NDDs with extensive COVID-19 restrictions implemented across Canada and the absence of alternative measures to support families and children in response to these restrictions. These findings are in alignment with studies which have described an increase in mental health challenges experienced by families of children with NDDs (Bentenuto et al, 2021 ; Breaux et al, 2021 ; Cluver et al, 2020 ; Gadermann et al, 2021 ; Lee et al, 2021 ; Patrick et al, 2020 ; Shorey et al, 2021 ; Yusuf et al, 2022 ). Our study further explored caregivers’ perspectives on the impact of COVID-19 policies and restrictions on their child and family experiences during the pandemic.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mental health challenges were experienced by parents and children with NDDs with extensive COVID-19 restrictions implemented across Canada and the absence of alternative measures to support families and children in response to these restrictions. These findings are in alignment with studies which have described an increase in mental health challenges experienced by families of children with NDDs (Bentenuto et al, 2021 ; Breaux et al, 2021 ; Cluver et al, 2020 ; Gadermann et al, 2021 ; Lee et al, 2021 ; Patrick et al, 2020 ; Shorey et al, 2021 ; Yusuf et al, 2022 ). Our study further explored caregivers’ perspectives on the impact of COVID-19 policies and restrictions on their child and family experiences during the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…During the pandemic, mental health implications for families caring for children with NDDs were also documented (Bentenuto et al, 2021 ; Cluver et al, 2020 ; Gadermann et al, 2021 ; Guller et al, 2021 ; Lee et al, 2021 ; Patrick et al, 2020 ; Shorey et al, 2021 ; Wang et al, 2021 ). The literature demonstrated that children’s mental health was impacted, though studies also showed an increased in resilience and behaviour for some children, related to reduced outings, simpler routines, and less transitions during lockdown and confinement (Yusuf et al, 2022 ). Despite these studies, there is still a limited understanding of how specific policies and pandemic restrictions impacted the mental health and overall functioning of children with NDDs and their parents in different regions and jurisdictions.…”
Section: Introductionmentioning
confidence: 99%
“…This study looked at multiple domains of functioning, including nutrition and access to school. The study found that if a parent could help their child cope with the pandemic including getting them access to schooling and finding "silver lining" activities to do with their child, they were most likely to fall into what the researchers called a "Resilient profile" and they had limited decreases across all domains (22).…”
Section: Impact On Cyshcn and Their Families Mental Healthmentioning
confidence: 99%
“…In spite of these widespread challenges, some families of students with SENDs reported certain positive outcomes from the school closures, such as spending more time together [ 18 , 33 ] and increased flexibility [ 29 ]. Qualitative and quantitative studies of students with SENDs identified that families who practiced coping skills—including implementing routines and structure [ 18 , 34 , 34 ], time management/organization [ 17 ], behavioral reinforcement [ 33 ], and those who leveraged technology to facilitate home-school communication and social support [ 34.∗ , 35.∗∗ , 36 , 37 ]—were most protected against academic problems and promoted adaptive functioning and mental health. Although it is well recognized that positive home-school communication is protective for students with SENDs, family engagement and advocacy efforts in support of youth with SENDs is typically shaped by inequality for historically minoritized students and families.…”
Section: Structural Barriers and Sources Of Covid-19 Learning Lossmentioning
confidence: 99%
“…The closure of schools and sustained disruption of typical schooling in response to COVID-19 has put a strain on children and families, heightening mental health issues and highlighting the necessity of extended school services, particularly for students with SENDs. In some communities, services for students with SENDs were adequate and met the need, while in others—particularly among under-resourced, racially, and ethnically minoritized populations—services were severely lacking [ 4 , 31 , 35 ]. COVID-19 made existing disparities more pronounced.…”
Section: Call To Action: Recommendations For Schools and Educational ...mentioning
confidence: 99%